2015
DOI: 10.3233/ch-141898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcutaneous application of gaseous carbon dioxide on cutaneous microcirculation

Abstract: Our results confirm a local vasodilatory effect of applied CO2 therapy. This finding indicates its potential clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
1
21
0
4
Order By: Relevance
“…Furthermore, exercise training has been shown to induce collateral circulation for increasing the blood supply and maintaining the function of the ischemic muscle (Hoier et al 2010;Kehler et al 2013;Milkiewicz et al 2005;Schirmer et al 2015). In addition, both clinical and experimental investigations have indicated the beneficial effects of CO 2 therapy for promoting the blood flow to the ischemic limb in peripheral artery D r a f t disease (Dogliotti et al 2011;Finzgar et al 2015;Hartmann et al 1997aHartmann et al , 1997bIrie et al 2005;Izumi et al 2015;Nishimura et al 2002;Pagourelias et al 2011). However, extensive research work is needed to understand the mechanisms of CO 2 -induced increase in blood flow in the ischemic skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exercise training has been shown to induce collateral circulation for increasing the blood supply and maintaining the function of the ischemic muscle (Hoier et al 2010;Kehler et al 2013;Milkiewicz et al 2005;Schirmer et al 2015). In addition, both clinical and experimental investigations have indicated the beneficial effects of CO 2 therapy for promoting the blood flow to the ischemic limb in peripheral artery D r a f t disease (Dogliotti et al 2011;Finzgar et al 2015;Hartmann et al 1997aHartmann et al , 1997bIrie et al 2005;Izumi et al 2015;Nishimura et al 2002;Pagourelias et al 2011). However, extensive research work is needed to understand the mechanisms of CO 2 -induced increase in blood flow in the ischemic skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Although CO 2 is a powerful vasodilator (Finzgar et al 2015;Ito et al 1989), it is highly unlikely that the observed increase in blood flow by CO 2 water-bath therapy in diabetic ischemic group under the experimental conditions of this study is due to any direct effect of CO 2 on blood vessels. Furthermore, alternation in blood viscosity cannot be considered to explain the improvement in blood flow (Dhalla et al 2017) in the diabetic ischemic group because the plasma levels of cholesterol triglyceride, HDL, and glucose were not affected by the CO 2 water-D r a f t bath therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Najubjedljiviji dokazi postoje za primjenu kineziterapije koja povećava gustinu intraepidermalnih nervnih vlakana, kapacitet regeneracije i funkciju perifernih nerava, smanjuje bol i umor i poboljšava funkcionalni ishod neuropatije (uključujući ravnotežu, rizik od pada i parametre hoda) [22][23][24][25]. Od ostalih modaliteta fizikalne terapije, najčešće se primjenjuju transkutana električna nervna stimulacija (TENS), magnetoterapija i galvanske kupke [26][27][28][29], dok su vakumkompresivna terapija i karbo tretman manje primjenjivani i istraživani u liječenju dijabetesne polineuropatije [30][31][32]. U studiji koja je poredila efikasnost primjene kombinovanih fizikalnih procedura (stabilna galvanizacija, impulsno elektromagnetno polje, transkutana električna nervna stimulacija-TENS i kineziterapija) u odnosu na liječenje alfaliponskom kiselinom, nađeno je da obe metode liječenja poboljšavaju elektromioneurografske parametre (brzinu provodljivosti kroz n. peroneus i n. suralis) kod bolesnika sa dijabetesnom neuropatijom.…”
Section: Discussionunclassified